S.O.S for a billion : the conquest of iodine deficiency disorders - Hetzel, Basil S.; Pandav, C.S. (New Delhi : Oxford University Press, 1996)
Iodine deficiency has been identified as a major and common preventable cause of mental defect in today's world. This book examines the need for a co-ordinated global strategy to tackle this menace in the affected countries and the success of this programme through agencies like UNICEF, and WHO.
Includes index.
Keywords: Iodine deficiency diseases; Iodine deficiency diseases -- Prevention